Examining the validity of parental alienation syndrome. Issue 2 (2nd July 2016) - O'Donohue, William; Benuto, Lorraine T.; Bennett, Natalie
ABSTRACT: "Parental alienation syndrome" (PAS) is a phrase first coined by Dr. Richard Gardner. Since its inception several scholars have reviewed and criticized this construct, and it has never been accepted by the scientific community as a legitimate scientific construct, as a syndrome or as a mental disorder. Despite its general rejection as unscientific, the construct of PAS at times continues to be used in legal settings as if it has an adequate foundation within science, clinical, or forensic practice. This commentary briefly reviews past critiques of PAS and describes several additional problems that have occurred with the use of this construct.